Distribuição do DNA dos herpesvírus bovino tipos 1 (BHV-1) E 5 (BHV-5) no encéfalo de coelhos durante a infecção latente - Mayer-winkelmann, Sandra Vanderli (2005)
Bovine herpesvirus type 5 (BHV-5) is a major etiologic agent of meningo-encephalitis in cattle and establishes lifelong latent infection in trigeminal ganglia and also in other areas of the brain. Colonization of deep areas of the brain with latent viral DNA may have important implications on the pathogenesis of BHV-5 neurological infection upon reactivation. In this study, we investigated the distribution of BHV-5 DNA in the brain of experimentally infected rabbits a laboratory model for BHV-5 infection - prior and subsequently to virus reactivation, using a nested PCR for the glycoprotein B gene. Eighteen rabbits inoculated intranasally with a Brazilian BHV-5 isolate were divided in two groups: group A rabbits (n=8) were euthanized 60 days post-inoculation (pi) for tissue collection; group B (n=7) were submitted to dexamethasone administration at day 60pi for reactivation of latent infection and euthanized for tissue collection 60 days later. To compare, we used two groups of BHV-1-infected rabbits (C, n=3 and D, n=3), each group being submitted to one of the above treatments, respectively. In group A rabbits, viral DNA was consistently detected in trigeminal ganglia (8/8), frequently in cerebellum (6/8), anterior cortex, pons medulla (3/8) and only occasionally in thalamus (2/8), ventro-lateral, dorsal and posterior cortices, midbrain (1/8). In rabbits previously submitted to virus reactivation, viral DNA showed a broader distribution, being detected more frequently besides the TG (7/7) - in ventro-lateral (6/7) and posterior cortices (5/7), pons-medulla and thalamus (4/7) and midbrain (3/7). In contrast, rabbits inoculated with BHV-1 harbored latent viral DNA in a few tissues in addition to TG and did not show significant changes in distribution of viral DNA post-reactivation. These results demonstrate that latency by BHV-5 DNA and not BHV-1 DNA may be established in several areas of the brain of experimentally infected rabbits. Further, dexamethasone-induced virus reactivation is followed by a wider distribution of latent viral DNA, probably due to virus dissemination from the original sites. Thus, it is reasonable to speculate that reactivation of latent infection from deep areas of the brain may contribute to the recrudescence of neurological disease frequently observed upon reactivation of latent BHV-5 infection.